bài 1
a) 3x^2 - 6x = 3x(x - 2)
b) x^2 - 2x + 1 - y^2 = (x^2 - 2x+1) - y^2 = (x-1)^2 - y^2=(x-y-1)(x+y-1)
c) 9x^3 - 9x^2y - 4x + 4y = 9x^2(x-y) - 4(x-y) = (9x^2 - 4)(x - y)=[(3x)^2 - 2^2](x-y)
=(3x-2)(3x+2)(x-y)
d) x^3- 2x^2 - 8x = x(x^2 - 2x - 8) = x(x^2 - 4x + 2x - 8)
= x[x(x - 4) + 2(x - 4)] = x(x + 2)(x - 4)
bài 2
a) x(x - 1) - x^2 + 2x = 5
<=> x^2 - x - x^2 + 2x = 5
<=> x = 5
b) 4x^3 - 36x = 0
<=> 4x(x^2 - 9) = 0
<=> 4x(x - 3)(x + 3) =0
<=> x = 0 hoặc x = +3
c) 2x^2 - 2x = (x - 1)^2
<=> 2x(x - 1) - (x - 1)^2 = 0
<=> (x - 1)(2x - x + 1) = 0
<=> (x - 1)(x + 1) = 0
<=> x = +1
d) (x - 7)(x^2 - 9x + 20)(x - 2) = 72
<=> (x^2 - 9x + 14)(x^2 - 9x + 20) = 72
<=> (x^2 - 9x + 14)^2 + 6(x^2 - 9x + 14) - 72 = 0 ( đoạn này bấm máy cho nhanh nhé)
<=> x^2 - 9x + 14 = 6 hoặc x^2 - 9x + 14 = -12
<=> x^2 - 9x + 8 = 0 hoặc x^2 - 9x + 26 = 0 (vô nghiệm , vì delta < 0)
<=> x = 1 hoặc x = 8